POLA KOMUNIKASI PASANGAN PERNIKAHAN PERIODE AWAL DALAM MEMBANGUN KETAHANAN KELUARGA (ANALISIS HABITUASI-NORMATIF) - Rahima Nawa Azkiya (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2024)
This study aims to determine the relationship between communication patterns and family resilience, especially in families in early marriage. This research is qualitative research using the field research method. The results of this study reveal that there is a correlation between family communication in determining family resilience. Based on the communication patterns found in this study, it can be seen that husbands and wives maintain communication relationships with each other, indirectly each partner understands that communication is very influential on the state of the family from all aspects. Based on the communication pattern, it illustrates that family resilience as stated in article 1 (11) of Law No. 52 of 2009 concerning population development and family welfare development is an indicator of family communication. Especially for families/partners in early marriages, communication must be strictly maintained because the family is still in the process of adjustment, and prone to conflict, maintaining communication is the best solution. Families that have good communication (with various existing patterns) can affect the condition of family resilience. So, if family resilience is achieved, the family goal can also be achieved, which is a harmonious and prosperous family.